SREDNJOVEKOVNO SRPSKO PRAVO O NASLEĐIVANJU - Šarkić, Srđan (Pravni zapisi, 2020)
Serbian legal sources have limited data on the law of wills and succession: no will was preserved and the Law Code of Stefan Dušan regulated intestate succession only in articles 41 and 48. It seems that the commoner class (sebri), living mostly in extended families, inherited their property according to the rules of customary law, while the noblemen accepted provisions of Byzantine law.In Serbian legal miscellanies, translated from Greek, the institutes of testate and intestate succession were thoroughly presented. The so called Zakon gradski (Serbian translation of Procheiron) contains 12 chapters referring to the law of succession and the Syntagma of Matheas Blastares placed all provisions on testate and intestate succession in chapter K – 12 under the title “On heirs and the disherison of sons or parents”.Byzantine law on intestate succession kept all the basic principles of Justinian’s legislation. Serbian sources only mention intestate succession of hereditary estates (so-called baština) belonging to the noblemen class, but according to some fragments from Serbian charters we can conclude that the estates could be inherited even in the commoner’s class. The fact that not a single will remained in Serbian mediaeval law does not mean that it was unknown in Serbia. Sources mention its existence using Slavonic terms “zavet” and “zaveštanije” and sometimes a Greek word “diatax”, while a freedom of disposition by testament was expressed by the formula “given for the soul” (“za dušu odati”).
Keywords: Law Code of Stefan Dušan; Procheiron; “Zakon gradski”; Syntagma of Matheas Blastares; testate succession; intestate succession; will